ANALISIS PENETAPAN HARGA DAN PENILAIAN OPSI PADA PERUSAHAAAN - Dewi Ratnasari Djou; Vevi Rahmawati Pudjiono; Sindi Ali; Maratusaleha Maratusaleha (LP2M Universitas Bina Bangsa, 2021)
This research aims to analyze pricing and option assessment on a company. Based on these objectives, researchers used a qualitative descriptive type of research. The source of the data in this study is secondary data derived from a variety of literature, documents and other written materials directly related to this research as well as information from various media. Data Collection Method used in this study is Documentation where is a method of data collection by looking for things or variables with the form of defects, books, newspapers, media and so on. The collected data is then processed with interpretive qualitative analysis. Data processing, taking place in conjunction with the data collection process, through 3 stages of data reduction, data presentation, and data verification. The results of this study can be concluded that the pricing and assessment of options at the company is to import a car worth DM1,000,000 cars from Germany and paid for in the next three months. forward rate Rp4,750,-/DM for hedging the possibility of strengthening marks in the future or have to buy options-buy marks with exercise price Rp4,750,-/DM with maturity in the next three months. Suppose the premium option-buy marks is Rp25,-/DM, then payoff profile. If the importer chooses to use forward there is a possibility that if marks at the time of payment depreciate against the rupiah to Rp4,600,-/DM then the importer must still pay marks at a price of Rp4,750,-/DM. Importer suffered a loss of Rp150,-/DM. If using the option-buy marks then the maximum loss is only Rp25,-/DM, because the importer does not need toexercise his options if the spot rate marks are Rp4,600,-/DM. There are several factors that affect the value of an option are: 1) The price of the stock or its underlying asset, 2) Exercise Price, 3) Interest Rate, 4) The period will be due and 5) The volality of the share price or asset price.